Design and Control of Fast Steering Mirror for Satellite Communication Process - Kim, Hyuntae; Jeon, Yongho; Gu Lee, Moon (2024 13th International Conference on Control, Automation and Information Sciences, ICCAIS 2024, 2024)
Free Space Optical (FSO) communication is emerging as a method of exchanging desired information over long distances like outer space. To achieve this, the transmitting and receiving units located over a long distance must be aligned each other. There are many disturbances in free space that can interfere with the alignment. Therefore, a Fast-Steering Mirror (FSM) mechanism is applied to correct the misalignment with high precision. In this study, we designed a FSM mechanism to achieve precise beam alignment between the transmitter and receiver in optical communication systems. The mechanism has a Voice Coil Motor (VCM) as an actuator, cartwheel hinge as a rotational guide, and laser displacement sensors as tip/tilt motion sensor. The VCM was designed based on magneto static analysis to have sufficient actuating force in the mechanisms' motion range. The sensors was properly placed perpendicular to the mirror to measure tip/tilt motion of the mechanism. In particular, the guide was designed with a cartwheel hinge that has sufficient stiffness despite its small size to ensure wide control bandwidth. The design was performed using optimization techniques, and the result was confirmed using the finite element method. The control results indicated a wide tilt range of 1.5 0, a high resolution of 0.005 0, and a small steady state error of 1 %. This approach can offer improvements in the performance of laser beam alignment. Enhancing alignment accuracy and reduced error of the FSM mechanism are also expected to be beneficial such as LIDAR and telescope.
Keywords: Cartwheel flexure; Communication process; Design and control; Fast-steering mirrors; Mirror mechanisms; Satellite communications; Sensor kinematic; Tilt motion; Tip-tilt; Voice coil motors; Cartwheel Flexure; Compliant Mechanism; Fast Steering Mirror; Sensor Kinematics; Voice Coil Motor